2006
DOI: 10.1002/gps.1710
|View full text |Cite
|
Sign up to set email alerts
|

Depression is associated with low plasma Aβ42 independently of cardiovascular disease in the homebound elderly

Abstract: Depressive symptoms are associated with low plasma Abeta42 independently of CVD. Prospective studies are needed to determine whether depression associated with low plasma Abeta42 is a separate depression subtype that could predict the onset of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 35 publications
(43 reference statements)
2
65
0
Order By: Relevance
“…Qiu 15 and Sun et al 16,17 reported large sample studies of plasma Ab in elderly subjects with depression. Sun et al measured plasma Ab40 and Ab42 in elderly subjects with depression (n = 101) and without depression (n = 223) in the absence of cardiovascular disease (CVD).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Qiu 15 and Sun et al 16,17 reported large sample studies of plasma Ab in elderly subjects with depression. Sun et al measured plasma Ab40 and Ab42 in elderly subjects with depression (n = 101) and without depression (n = 223) in the absence of cardiovascular disease (CVD).…”
Section: Discussionmentioning
confidence: 99%
“…Another study using 515 elderly subjects (161 depressed, 354 non-depressed) demonstrated similar results, and showed that depressive symptoms were associated with low plasma Ab42 independent of CVD in elderly subjects. 15 In that investigation, CVD was used to indicate vascular depression, 25 and the subtype of elderly subjects with depression associated with Ab was considered to show 'amyloid-associated depression' as opposed to vascular depression. More recently, the same group …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a few data are available regarding the relationship between depression and peripheral levels of Aβ peptides. Higher levels of Aβ40, lower levels of Aβ42, and a greater Aβ40/Aβ42 ratio have been reported in elderly patients with depression, as compared with healthy control subjects [18,19,20]. Moreover, the study by Sun et al [20] highlighted how the so-called ‘amyloid-associated' depression (with high Aβ40/Aβ42 ratio) is characterized by a more severe deficit in memory, visual-spatial skills, and executive functions.…”
Section: Introductionmentioning
confidence: 99%